A Comparative Analysis of Fatigue Resistance in Asphalt Wearing Courses Modified with 7% Content of Natural Rubber and Waste Tire Rubber - Hendrik Jimmyanto; Ramadhani Ramadhani; Rindu Twidi Bethary; Lega Lubis Reskita; Kiagus Muhammad Aminuddin (JURUSAN TEKNIK SIPIL, 2026)
Fatigue cracking remains a primary structural failure in flexible pavements, necessitating the development of more ductile and resilient asphalt mixtures. This study investigates the fatigue performance of Asphalt Concrete-Wearing Course (AC-WC) modified with 7% natural rubber and waste tire rubber, specifically comparing Pre-vulcanized Latex (LP7) and a combination of solid natural rubber and crumb rubber (KACR 7) against a conventional 60/70 penetration grade asphalt (Aspen). The experimental program employed the Indirect Tensile Fatigue Test (ITFT) under a controlled-stress mode of 500 kPa at 20°C to evaluate stiffness degradation, horizontal deformation, and cumulative strain. The results indicate that the 7% rubber modification induces a significant